Occupational exposure to chlorophenates. Renal, hepatic and other health effects. - Enarson, D. A.; Chan-Yeung, Moira; Embree, V.; Wang, R.; Schulzer, M. (Scandinavian Journal of Work, Environment & Health, 1986)
A group of 71 chlorophenate-exposed sawmill workers were identified as part of a group undergoing an extensive health and environmental evaluation in a pulp mill. This group was compared with a group (N = 351) with no physical proximity to the area in which chlorophenates were used. Exposure was higher for those directly handling the wood and lower for those working in the area but not handling the wood. Those with chlorophenate exposure were not significantly more likely to report a history of jaundice or liver, kidney or heart disease. Moreover, the serum creatinine, bilirubin, glutamic oxaloacetic transaminase (GOT), and alkaline phosphatase values did not differ from those of the reference group. The hemoglobin level was similar in the three groups. But the peripheral blood leukocyte count was marginally lower in the exposed groups and their hematocrit was reduced, significantly so for the heavily exposed group. Urinalysis showed an increased prevalence of microscopic hematuria, especially with lower cell counts. No unequivocal explanation is available for the reduced hematocrit or the low level of hematuria.